Analisis Pengaruh Status Kurang Gizi Pada Balita - Darmi Arda; Nursyamsi Norma Lalla; Suprapto Suprapto; Andi Agustang (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: Nutritional status is a significant thing that parents must know, especially those with toddlers because it is a golden age related to growth and development in the future. Objective: Knowing the relationship analysts of malnutrition status in toddlers. Method: The research design uses a descriptive-analytical approach using the Cross-Sectional study approach. Results: the chi-square test shows a diet of p:0.000 values and knowledge of p:0.01 values. Conclusion: The mother's diet and learning affect the nutritional status of toddlers. For mothers to increase understanding by continuously participating in counselling about health, especially the nutritional status of toddlers, and health workers, further improve counselling for families, health counselling, and health services